The Maritain Factor : Taking Religion into Interwar Modernism - De Maeyer, Jan, 1952-; Heynickx, Rajesh, 1977- (Book collections on Project MUSE., 2010)
By studying the reception and perception of the French Catholic philosopher Jacques Maritain, this book argues that European modernist artists and intellectuals sought a primordial finality in Catholicism. The French poet, writer, and surrealist filmmaker Jean Cocteau converted under the influence of Maritain. For the painters Gino Severini, a pioneer of Futurism, and Otto Van Rees, one of the first Dadaists -both converts- Maritain played the role of spiritual counselor. And when the promoter of abstract art Michel Seuphor embraced Catholic faith in the 1930s, he, too, had extensive contact w.